Realidade transfigurada em poesia: a relação dialética criadora de João Cabral de Melo Neto - Deon, Robson (2019)
This work – focused on poetry – has the object of studying two poems of the modernist poet João Cabral de Melo Neto, O cão sem plumas (1950), and “Festa na casa-grande” (Dois Parlamentos, 1960). Both poems are critical and socially engaged because they approach social situations experienced in the Northeast of Brazil, being created as form of an interactionist perspective between the perception of social reality mixed and combined with style, to construction and to refinement poetic of the author. Therefore, the main intention is to recognize the intrinsic connection between the poetry and the reality in the poetic works, tracking the social aspects of the natural, geographic and human reality that are interiorized in them, in particular, understanding how the reality it is transmuted in poetry, and how it happens through human figures' configurations of mangrove man, in O cão sem plumas, and of sugarcane worker, in “Festa na casa-grande”. As relevant authors for the discussions, it stands out Bosi (2004), Candido (2004; 2006; 2011), Gullar (1978), Merquior (2007), Secchin (2007), Araújo (2019), and others. In contributions to the literary studies, this work exposes the poetry as a literary genre able to embrace the spectrum of the social, thus pointing the importance of sociological aspects as constituent’s elements and factors to the art, which besides providing the pleasure of beauty and aesthetic, it can also allow us the access to critical and deep knowledge of the society.